Brand Equity Review: Sales Promotion Role in Tropicana Slim Purchasing Decision - Michelle Michelle; Sugeng Wahyudi; Rustono Farady Marta (Komunikator, 2022)
As a top Indonesian product, Tropicana Slim seems to give new solutions to enjoying sweet taste widely used in Indonesian cuisine without worrying about the negative impacts often feared by the public, such as obesity and diabetes. Tropicana Slim’s achievements as the top brand for five years have several factors in consumer purchasing decisions that could lead to product loyalty under the Tropicana Slim brand. Therefore, this study aims to see the role of brand equity which consist of brand image, brand awareness, and sales promotion of Tropicana slim products introduced by PT Nutrifood Indonesia through their Instagram account @tropicanaslim leads to purchasing decisions. This research was carried out from March until April 2021 using a positivism paradigm with a quantitative approach and content analysis using visuals and text from 16 posts on their Instagram account. This research indicates the role of brand equity in the form of brand image with a frequency value of 42,03%, brand awareness with 26,09%, and sales promotion with a frequency of 31,88% on purchasing decisions. It can be concluded that the postings on the @tropicanaslim Instagram account take the role of elements of brand equity and sales promotion in purchasing decision process.